Social data interoperability in educational repositories and federations. (1st January 2013) - Rajabi, Enayat; Greller, Wolfgang; Niemann, Katja; Kastrantas, Kostas; Sanchez-Alonso, Salvador
Several standard metadata notations exist for content items (e.g., IEEE LOM) or persons (e.g., HR-XML). Additionally, a number of classes of metadata such as competence metadata, social metadata, etc. exist in ranges from strict vocabularies to folksonomies. For social metadata, however, several diverse schemata have been proposed, but no commonly agreed standard is available that describes the variety of interactions provided in socially powered platforms. In this paper, we propose a social metadata schema for repository federations containing educational resources (ER) which allows them to expose social data so they can be harvested and used by a variety of service providers. We base this schema on the analysis carried out in the context of the Open Discovery Space project, an EU funded initiative, which harvests information in the form of social metadata and encapsulates the user experience from several content providers' platforms and studies several solutions to their integration.